1990
DOI: 10.1247/csf.15.67
|View full text |Cite
|
Sign up to set email alerts
|

Purification of DNA ligases from mouse testis and their behavior during meiosis.

Abstract: ABSTRACT. Two types of DNAligase, I and II, have been purified approximately 4,000-fold from mouse testes and 500-fold from nuclei of mouse spermatocytes. DNAligase I and II consisted of single polypeptides with molecular weights of 95,000 and 65,000, respectively, according to the estimation by SDS-polyacrylamide gel electrophoresis and the AMP-bindingassay. Ligase activities were higher in premeiotic spermatogonia and spermatocytes than those in liver and bone marrow cells. Moreover, DNAligase II showed rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…This was the case for the first report on a mammalian DNA ligase activity (24) as well as for several more recent investigations (25)(26)(27)(28)(29). Other early studies reported on both the intact fonn and the active fragment of DNA ligase I (30).…”
Section: Dna Ligase I Structurementioning
confidence: 56%
See 4 more Smart Citations
“…This was the case for the first report on a mammalian DNA ligase activity (24) as well as for several more recent investigations (25)(26)(27)(28)(29). Other early studies reported on both the intact fonn and the active fragment of DNA ligase I (30).…”
Section: Dna Ligase I Structurementioning
confidence: 56%
“…A DNA ligase distinct from DNA ligase I is more firmly associated with cell nuclei and is only extracted into soluble form by salt-containing buffers (27,39,70). The enzyme has been purified from calf thymus as a 68-72-kDa protein of apparent homogeneity, estimated by SDS-polyacrylamide gel elec trophoresis, by three different groups (27,45,71).…”
Section: Dna Ligase IImentioning
confidence: 99%
See 3 more Smart Citations